2021
DOI: 10.2196/24643
|View full text |Cite
|
Sign up to set email alerts
|

Expectations of Health Researchers From Academic Social Network Sites: Qualitative Study

Abstract: Background Today, academic social network sites' role in improving the quality of education and how investigators conduct their research has become more critical. Objective This study aimed to investigate Iranian health researchers' requirements for academic social network sites from a low-income country perspective. Methods This qualitative study with a phenomenological approach was done in 2020. In this st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Kong found that the use of new technologies can play a role in attracting new users (15). Some other research on researcher needs also found that the intelligence of academic social networks can affect other network functions (16).…”
Section: Discussionmentioning
confidence: 98%
“…Kong found that the use of new technologies can play a role in attracting new users (15). Some other research on researcher needs also found that the intelligence of academic social networks can affect other network functions (16).…”
Section: Discussionmentioning
confidence: 98%
“…This qualitative study was conducted to identify barriers to the implementation and development of THC in 2022. Due to the different conditions in Iran and the lack of information in this study, a qualitative method was used to show the experiences, knowledge, and implicit information of the participants also in this study, due to the lack of a complete theory, the content analysis was used (19).…”
Section: Methodsmentioning
confidence: 99%